STUDY ON THE PREVALENCE, CLINICAL AND PARACLINICAL CHARACTERISTICS, CAUSES, AND PREGNANCY OUTCOMES IN PREGNANT WOMEN WITH OLIGOHYDRAMNIOS AT DONG NAI 2 HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2026)
Background: Abnormalities of amniotic fluid volume, including both polyhydramnios and oligohydramnios, may increase maternal and perinatal morbidity and mortality. Among these, oligohydramnios is a significant risk factor that directly affects fetal development and contributes to a higher likelihood of labor complications or the need for cesarean delivery. Oligohydramnios is defined as a reduction in amniotic fluid volume relative to gestational age.Objectives: To determine the prevalence, clinical and paraclinical characteristics, causes of oligohydramnios, and to evaluate pregnancy outcomes in women with oligohydramnios at Dong Nai 2 Hospital in 2025. Materials and Methods: This case-series study included 77 pregnant women with oligohydramnios identified among 650 pregnant women with a gestational age of more than 28 weeks who met the study inclusion criteria. Results: The prevalence of oligohydramnios in this study was 11.85%. The mean maternal age was 29.25 ± 5 years, with women aged 20 to
Keywords: Oligohydramnios, cesarean section.